Las estrategias metodológicas y su incidencia en el aprendizaje de los niños y niñas de 4 años de edad de la unidad Educativa República de Francia de la cuidad de Santo Domingo de los Tsáchilas. Periodo lectivo 2013-2014 - Enriquez Bravo, Dolores del Rosario (2014)
This thesis refers to “METHODOLOGICAL STRATEGIES AND THEIR IMPACT ON LEARNING CHILDREN OF 4 YEARS OF AGE EDUCATION UNIT “FRENCH REPUBLIC " OF THE CITY OF SANTO DOMINGO DE TSÁCHILAS. LECTIVO PERIOD 2013-2014” The general objective was: To determine the incidence of the approaches to learning of teachers in the Joint " Republic of France " Fiscal School in the city of Santo Domingo de los Tsáchilas, through direct observation and implementation of surveys. The methods used for the preparation of this research work were : Scientist, Hypothetical Deductive , Synthetic Analytical , Statistical Model ; the techniques used were: a survey that was applied to the teachers to collect information about the problems of incorrect or non-use of the Methodological Strategies that harm the learning process of children and Test Functions and basic applied to children which I allowed to evaluate their skills , to determine their level in the teaching-learning process Test of Basic Functions, applied to children, was obtained as a result: Of the children who were administered the Test of Basic Functions, 82% obtain good activities and 18% did not. In the implementation of the survey of teachers concluded that: Teachers report that in the process of Teaching Instructional Strategies handled as 50% socialization strategies used, 25% Strategies Project and the other 25 % use all Insertion strategies, Project, Field and Socialization.